Pemberdayaan Masyarakat melalui Peran UKM Batik Canting Bekasi - Nurul Imamilkhoir; Syamsuddin RS; Dedi Herdiana (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
This study aims to analyze the efforts of community economic empowerment, the implementation process to the results of community economic empowerment carried out by the Batik Canting Bekasi SMEs. This study used a descriptive method, while the approach used in this study was a phenomenological approach. The author borrows the theory of empowerment according to Eddy which states that empowerment is an effort to develop community potential into real action. The results showed that community economic empowerment carried out by batik canting SMEs was through a batik training program about batik and its characteristics, a system of providing insightful knowledge and batik material. The process of implementing the training goes through the planning stage, the implementation stage to the monitoring and evaluation stage. The results of the empowerment can increase the insight and skills of the community, the emergence of member participation in empowerment activities and improve the community's economy.